A new method for evaluating nominal operating cell temperature (NOCT) of unglazed photovoltaic thermal module - Vat Sun; Attakorn Asanakham; Thoranis Deethayat; Tanongkiat Kiatsiriroat (Energy Reports, 2020)
Photovoltaic thermal (PVT) modules convert solar energy into electricity and heat. Unlike that of normal photovoltaic modules, the nominal operating cell temperature (NOCT) of PVT modules, which is used to evaluate the temperature and electrical power output, is unknown because it depends on the mass flow rate and inlet temperature of the working fluid in the module. In this paper, a new method for calculating the NOCT of PVT modules with water as the working fluid is presented. Four unglazed identical PVT modules in series were tested outdoors with various mass flow rates. The tests, which were similar to solar collector tests, were conducted from 8:30 to 16:30 on clear-sky days in Chiang Mai, Thailand, and the water inlet temperature of the first PVT module of the system was varied from 27 to 60~°C. The correlation between the NOCT of the unglazed PVT module, based on (Tfi-Ta)/IT, and the water mass flow rate, çm, was determined. The calculated PVT module temperature determined with the new NOCT method agrees well with the experimental data, and 96% of the calculated results deviate only by up to ±10% from the experimental data.
Keywords: 330; Module temperature; Nominal operating cell temperature; Performance; Photovoltaic thermal module